Comparison of the Effectiveness and Mechanism of Effect of Acceptance and Commitment Therapy Based on Emotion-Focused Therapy on Sexual Health in Patients with Type 2 Diabetes: The Role of Psychological Flexibility and Emotional Efficiency - Mojgan Zandi; Shahram Mohammad Khani; Mohammad Hatami (پژوهش‌های کاربردی روانشناختی)
The aim of this study was to compare the effectiveness and mechanism of acceptance and commitment-based therapy and emotion-focused therapy in the context of sexual health in type 2 diabetic patients, with a particular emphasis on the influence of psychological flexibility and emotional efficiency. The present study was quasi-experimental with pretest-posttest with a control group. The statistical cohort consisted of all patients with type 2 diabetes who were referred to the endocrinology clinics of Tehran University of Medical Sciences in 2019. Three groups of 15 were randomly selected from the forty-five eligible individuals and volunteers who were selected using the cluster sampling method: acceptance and commitment-based therapy, emotion-focused therapy, and witness-based therapy. The Larson Sexual Satisfaction Questionnaire (LSSQ), Emotion Efficacy Scale (EES), and Acceptance and Action Questionnaire (AAQ) comprised the research instrument. Acceptance and commitment-based therapy was performed as a group for 12 60-minute sessions and emotion-focused therapy as a group for 8 60-minute sessions. Data were analyzed using SPSS-26 software and covariance analysis. Probability values of 0.05 were analyzed. The findings indicated that the variables of psychological flexibility and emotional efficiency serve as mechanism variables (P <0.05). The study’s findings indicate that the sexual health of patients with type 2 diabetes is influenced by acceptance and commitment-based therapy and emotion-focused therapy, which are characterized by psychological flexibility and efficacy.